2015
DOI: 10.1063/1.4922662
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and kinetic models for spin-1/2 electron-positron quantum plasmas: Annihilation interaction, helicity conservation, and wave dispersion in magnetized plasmas

Abstract: We discuss complete theory of spin-1/2 electron-positron quantum plasmas, when electrons and positrons move with velocities mach smaller than the speed of light. We derive a set of two fluid quantum hydrodynamic equations consisting of the continuity, Euler, spin (magnetic moment) evolution equations for each species. We explicitly include the Coulomb, spin-spin, Darwin and annihilation interactions. The annihilation interaction is the main topic of the paper. We consider contribution of the annihilation inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 98 publications
0
30
0
Order By: Relevance
“…It is similar to the spinless case when the continuity and Euler equations can be represented as the single fluid effective non-linear Schrodinger equation [53]. Even spin-orbit interaction [19] and other relativistic effects [22], [58] can be included in non-linear effective equations. Nonlinearity is caused by different factors: the many-particle interaction effect and the pressure, particularly the Fermi pressure.…”
Section: A Non-linear Pauli Equationmentioning
confidence: 99%
“…It is similar to the spinless case when the continuity and Euler equations can be represented as the single fluid effective non-linear Schrodinger equation [53]. Even spin-orbit interaction [19] and other relativistic effects [22], [58] can be included in non-linear effective equations. Nonlinearity is caused by different factors: the many-particle interaction effect and the pressure, particularly the Fermi pressure.…”
Section: A Non-linear Pauli Equationmentioning
confidence: 99%
“…Among them we find the appearance of the spinplasma waves with frequencies near the cyclotron frequency [3], [4], [5], [6]. Later it was demonstrated that the quantum Bohm potential existing in the magnetic moment evolution equation shifts the frequency of the spin-plasma waves [7], [8]. This shift is proportional to the square of the wave vector.…”
Section: Introductionmentioning
confidence: 97%
“…Spin parts of the vorticity and helicity for spin-1/2 electron-positron plasmas were obtained in Ref. [8]. These phenomena appear along with the change of properties of well-known plasma phenomena (see for instance Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hydrodynamic and kinetic models for spin-1/2 electron-positron quantum plasmas has been developed in Ref. [37] which incorporates the Coulomb, spin-spin, Darwin and annihilation interactions. There was concluded that the contributions of the annihilation interactions shifts the eigenfrequencies of the transverse electromagnetic plane polarized waves and transverse spin-plasma waves.…”
Section: Introductionmentioning
confidence: 99%